THE INFLUENCE OF CAPITAL STRUCTURE, ASSET GROWTH AND PROFITABILITY ON STOCK PRICES IN THE TRANSPORTATION SECTOR OF AIRLINES REGISTERED ON THE IDX, 2018-2022: THE INFLUENCE OF CAPITAL STRUCTURE, ASSET GROWTH AND PROFITABILITY ON STOCK PRICES IN THE TRANSPORTATION SECTOR OF AIRLINES REGISTERED ON THE IDX, 2018-2022 - Zulkarnain, Iskandar; Hanifah, Azimah; Ahmad, Gatot Nazir (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This research was conducted with the aim of finding out and analyzing the influence of Capital Structure, Asset Growth and Profitability on Share Prices in the Airline Transportation Sector listed on the IDX in 2018-2022. This research is quantitative research that is associative in nature. The population in this study are companies operating in airline transportation in 2018-2022. Sampling was carried out using techniques of non probability sampling or a saturated sample, namely using all sample airline companies. The data technique used in this research is Multiple Linear Regression Panel Data using Eviews 10 software. The results of this research show that partially Capital Structure (DAR) has no effect and is not significant on stock prices, Asset Growth has no effect and is not significant on stock prices, and Profitability (ROA) has a positive and significant effect on stock prices.